The water flow diagram - Bouman, Lukas; Spuhler, Dorothee; Bünzli, Marc-André; Melad, Amancio; Diop, Lamine; Coelho, Osmar; Meierhofer, Regula (Frontiers in Water, 2024)
Introduction The Water Flow Diagram (WFD) is a novel advocacy and communication tool that presents urban water supply and management in a simple visualization. Rapid urbanization, growing populations, and the climate crisis increase the pressure on water resources, particularly in urbanized areas. The WFD aims to foster a dialogue around conflict of interests and opportunities among different stakeholders, and trigger actions toward more sustainable urban water management (UWM), as well as a water secure future. Method The WFD is produced from data on water abstraction, water use of different sectors, water treatment, water recycling and contamination risks. The data were obtained from government services, wastewater and water utilities, large industries, universities and reports of intergovernmental organizations. If these sources did not have data, reports from NGOs or consultants, comparable contexts, default values or expert judgements were considered. The annual water flows are presented in a Sankey Diagram. An intuitive color code highlights the flows as “problematic” or “appropriate” and points to areas where UWM practices should be improved. Results and conclusions The final diagrams are a concise instrument that identifies challenges of UWM in the four application cases presented in this article. Key challenges that became evident included: pollution from agricultural production, the lack of wastewater and sanitation infrastructure, high water losses in the distribution networks, water exports leading to a lack in local supply and sewer overflows during heavy rainfalls. Opportunities identified were the need to: invest in sanitation and wastewater to protect resources, create coordination bodies to align conflict of interests, and/or invest in blue-green infrastructure for rainwater retention. The WFD triggered local actions, such as in-depth discussions between relevant actors, the formation of integrated water use committees and the interest of the national ministry in Senegal to replicate the diagram for other locations. This article presents the methodology, discusses the four case studies and deliberates on the prospective use of the WFD.